Analisis Pengaruh Pemasangan Median Jalan Dan Tingkat Pelayanan Diruas Jalan Mayjen Harun Sohar Kota Pagar Alam - Edowinsyah Edowinsyah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
Road segment Mayjen Harun Sohar is one of the roads in Pagar Alam city that have not road facilities such as road markings, lane division and traffic separator (median road) that have potential traffic accidents. With the problem then in the formulation of the problem how the traffic characteristics of the road ?, how the level of service without median road? and what is the level of road service with the median road ?,This study aims to determine the characteristics of traffic, to know the level of service / performance of the road without median and to know the level of service / performance of the road with the median. The method used to analyze data using manual of road capacity indonesia (MKJI 1997), this research to get value of volume of traffic flow, road capacity, degree of saturation and level of service of road. From the research results obtained volume of traffic flow peak hour Qmaks = 1144.7 smp / hour. for road of type 2/2 UD is got value of road capacity (C) = 2610 smp / hour, value of degree of saturation (Ds) = 0,53 service level C, street type 4/2 UD obtained street capacity value (C) = 5508 smp / hour, value of degree of saturation (Ds) = 0,207 level of service B and road type of 4/2 D got value of road capacity (C) = 5816,45 smp / hour, value of degree of saturation (Ds) = 0,19 level of service A. so it can be concluded that with the installation of road median effect on road capacity, degree of saturation and level of service road.